Meningkatkan Semangat Kreaatifitas Masyarakat Melalui Pelatihan Pembuatan Kerupuk Tulang Ikan Di Kampung Pujodadi Kecamatan Trimurjo - Robi Santoso; Beny Hartawan; Ridho Aritonang; Tri Endang Yulianti (Lembaga Pengembangan Kinerja Dosen, 2024)
Pujodadi Village, Trimurjo District, Central Lampung Regency, Lampung Province, what was carried out in this activity included preparation, training and implementation of product manufacturing. The results achieved in implementing the community service program were increasing public knowledge about the benefits of fish bone waste, increasing knowledge in making fish bone crackers and providing a new product, namely fish bone crackers. The training in making catfish bone crackers really helped the Pujodadi community, especially the women of Hamlet 2. In this extension, the women of Hamlet 2 were very enthusiastic about this training. This training is carried out so that waste that is usually thrown away can be used into useful products that are ready to be sold.